Contacts in death: The role of the ER-mitochondria axis in acetic acid-induced apoptosis in yeast - Martins, Vítor M. (2019)
Endoplasmic reticulum-mitochondria contact sites have been a subject of increasing scientific interest since the discovery that these structures are disrupted in several pathologies. Due to the emerging data that correlate endoplasmic reticulum-mitochondria contact sites function with known events of the apoptotic program, we aimed to dissect this interplay using our well-established model of acetic acid-induced apoptosis in Saccharomyces cerevisiae. Until recently, the only known tethering complex between ER and mitochondria in this organism was the ER-mitochondria encounter structure (ERMES). Following our results from a screening designed to identify genes whose deletion rendered cells with an altered sensitivity to acetic acid, we hypothesized that the ERMES complex could be involved in cell death mediated by this stressor. Herein we demonstrate that single ablation of the ERMES components Mdm10p, Mdm12p and Mdm34p increases the resistance of S. cerevisiae to acetic acid-induced apoptosis, which is associated with a prominent delay in the appearance of several apoptotic markers. Moreover, abrogation of Mdm10p or Mdm34p abolished cytochrome c release from mitochondria. Since these two proteins are embedded in the mitochondrial outer membrane, we propose that the ERMES complex plays a part in cytochrome c release, a key event of the apoptotic cascade. In all, these findings will aid in targeted therapies for diseases where apoptosis is disrupted, as well as assist in the development of acetic acid-resistant strains for industrial processes.